Measles Cases by Age Group during the Elimination of Infection - O. V. Tsvirkun; A. G. Gerasimova; N. T. Tikhonova; E. B. Ezhlova; A. A. Melnikova; E. L. Dubovitskaya; O. S. Orlova; A. A. Basov; R. A. Frolov (Эпидемиология и вакцинопрофилактика)
Objective. With the increase in vaccination coverage of the child population began the process of ousting children determining the incidence of measles in the country and by 2004, the children ceased to play a leading role in maintaining the epidemic process of measles. The definition of significance in the epidemic process of measles individuals of different age, including children in the first year of life, was the purpose of the work. Material and methods. Measles cases in different age groups were analyzed for the period 2003 - 2015 in the Russian Federation. 1799 cases of measles in children under 1 year were investigated. The ELISA method were examined the sera of children up to 1 year in 2002 - 22 sampls, 2016 - 31 sampls. Results. Analysis of the incidence of measles in different age groups conducted since the beginning of the program of measles elimination in Russia to date (2003 - 2015), showed that with the increase in the level of the immune stratum, the incidence of measles inculcated among the population declined markedly and even in the boom years (2012 - 2014) intensive morbidity rates of children aged 3 - 6 years, adolescents and adults averages ranged from 3.0 to 4.0 per 100 thousand of the appropriate age. The exception was children first year of life and children aged 1 - 2 years, of intense the incidence of which was several times higher (in average, respectively, was 22.0 and 19.0). If the vast majority of affected children aged 1 - 2 years had been vaccinated against measles, for various reasons, the children of the first year of life, according to the immunization calendar, the vaccination could not be. Conclusion. Detailed analysis showed that the incidence of measles in the country determined by the adult population. Comparison of incidence and state of specific immunity to measles virus in children the first year of life suggests that their involvement in the epidemic process of measles is not determinative. Changing the proportion of affected children of this age are directly linked with fluctuations in the long-term dynamics of the overall incidence of measles in the country, and high, compared with other age groups, the intensive indicator of disease is not due to a large numerical composition of this age group.